2015
DOI: 10.1200/jco.2014.55.5714
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide Combined With R-CHOP Overcomes Negative Prognostic Impact of Non–Germinal Center B-Cell Phenotype in Newly Diagnosed Diffuse Large B-Cell Lymphoma: A Phase II Study

Abstract: R2CHOP shows promising efficacy in DLBCL. The addition of lenalidomide appears to mitigate a negative impact of non-GCB phenotype on patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
240
2
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(259 citation statements)
references
References 31 publications
4
240
2
10
Order By: Relevance
“…Early clinical data showed preferential activity in refractory/relapsed ABC vs. GCB DLBCL, with an overall response rate (ORR) of 53% and 9%, respectively [47]. Given these results, two studies adding lenalidomide to R-CHOP in newly diagnosed DLBCL have recently been completed [48,49]. Ibrutinib is an inhibitor of the Bruton Tyrosine Kinase (BTK), an important component of the B-cell receptor (BCR) pathway.…”
Section: Antiviral Therapy In Combination With Ebv Lytic Phase Inductionmentioning
confidence: 99%
“…Early clinical data showed preferential activity in refractory/relapsed ABC vs. GCB DLBCL, with an overall response rate (ORR) of 53% and 9%, respectively [47]. Given these results, two studies adding lenalidomide to R-CHOP in newly diagnosed DLBCL have recently been completed [48,49]. Ibrutinib is an inhibitor of the Bruton Tyrosine Kinase (BTK), an important component of the B-cell receptor (BCR) pathway.…”
Section: Antiviral Therapy In Combination With Ebv Lytic Phase Inductionmentioning
confidence: 99%
“…Az R 2 -CHOP (R-CHOP + lenalidomid 25 mg) alkalmazásával az ABC-csoportban a 2 éves túlélés 46%-ról 83%-ra nőtt. Ez a különbség nem látható a GCB-csoportban [42]. Ezen adatok alapján az ABC-altípus kezelésében a lenalidomid alkalmazása mindenkép-pen szóba jön.…”
Section: A Dlbcl Kezelése Maunclassified
“…The British Columbia Cancer Agency (BCCA) and colleagues reported that the non-GCB and GCB subtypes had a similar outcome in stage II-IV DLBCL treated with 6 cycles of R2-CHOP. 30 The Fondazione Italiana Linfomi group also reported that there was no difference in 2-year PFS (81% vs. 71%; p = 0.705) and OS (94% vs. 88%; p = 0.58) in patients with stage II-IV disease, 60-80 years of age, treated with 6 cycles of R2-CHOP between the non-GCB type and GCB type, with a median follow-up in survivors of 28 mon (REAL07). 31 Several clinical trials, such as phase III trials comparing R-CHOP and R2CHOP and trials consisting of lenalidomide maintenance therapy, have been conducted on untreated DLBCL.…”
Section: Immunomodulatory Drugsmentioning
confidence: 99%